I AM IMMORTAL. (16th November 2016) - Trezzi, Riccardo
Abstract : I suggest a model to forecast life expectancy based on the electrocardiogram signal. I show how the heart electrical activity can be decomposed in the state‐space and that the suggested model has superior out‐of‐sample properties compared to a set of alternatives. When the model is used to forecast my own electrocardiogram, a striking result arises: the n ‐step ahead forecast remains bounded and positive even after one googol period. Therefore, my life expectancy tends to infinity implying that I am immortal . ( JEL I10, I19)